Association of vitamin D deficiency with acute lower respiratory tract infections in newborns. (18th March 2016) - Dinlen, Nurdan; Zenciroglu, Aysegul; Beken, Serdar; Dursun, Arzu; Dilli, Dilek; Okumus, Nurullah
Abstract: Objective : To determine the association between serum 25-hydroxy vitamin D [25(OH)D] levels and acute respiratory tract infections (ALRTI) in newborns. Study design : The study group consisted of 30 term newborns with ALRTI who were admitted to our neonatal intensive care unit. Controls were 30 healthy newborns with the same age as the study group. Newborns and their mothers were tested for serum 25(OH)D levels, with a low level defined as ≤15 ng/mL. Results : The groups were similar in gestational week, birthweight, postnatal age and gender. Forty-three of the 60 infants (including study and control) had low 25(OH)D levels. The median 25(OH)D levels were lower [9.5 ng/mL (IQR = 7.9–12.2)] in the study group than those of the control group [15.5 ng/mL (IQR: 12–18)] ( p = 0.0001). The median serum 25(OH)D levels in the mothers of the study group were also lower than those in the mothers of the control group [11.6 ng/mL (IQR = 9.4–15.8) and 17.3 ng/mL (IQR = 13.7–20.6), respectively] ( p = 0.0001). Conclusion : Lower blood 25(OH)D levels might be associated with increased risk of ALRTI in term newborn babies. Appropriate vitamin D supplementation during pregnancy and early childhood may enhance newborns' respiratory health.